PENGARUH BRAND EQUITY SEPEDA MOTOR TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pengguna Sepeda Motor Honda Pada Mahasiswa Universitas Muhammadiyah Magelang) - Atul, Lukluk; Admadi, Jangkung (Universitas Muhammadiyah Magelang, 2006)
This is a research which observes the influence Brand Equity motorcycle?s to customer saisfaction to Honda?s user university student,. Muhammadiyah Magealang University, Brand Equity is measured through variabel such as brand loyalty, brand awareness, perceived quality, brand associations and other brand asstes. The result of research reveals taht Brand Equity to Honda?s user university student,. Muhammadiyah Magelang University tends to be good and tends to be high grade, there is a dominan variabel causal influence customer satisfaction, this the result f research, there?s a positive casual influence taht is a significant between Brand Equity Honda?s to customer satisfaction.